Case Report: Clinical and Pharmacokinetic Profile of Lithium Monotherapy in Exclusive Breastfeeding. A Follow-Up Case Series - Imaz, Maria Luisa; Soy, Dolors; Torra, Mercé; García-Esteve, Llüisa; Soler, Cristina; Martin-Santos, Rocio (Frontiers in Pharmacology, 2021)
Background: Most guidelines advise that women taking lithium should not breastfeed. The variation in transfer is just one reason behind this advice. Objectives: To present clinical and pharmacokinetic data of nine mother–infant pairs exposed to lithium monotherapy during late pregnancy and exclusive breastfeeding at the Perinatal Psychiatric Unit (2006–2018). Methods: We obtained sociodemographic data, medical risk factors, obstetric variables, and family and personal psychiatric history by semi-structured interview, and assessed maternal psychopathology with the Hamilton Depression Rating Scale and Young Mania Rating Scale. A senior neonatologist reviewed neonatal outcomes at birth using the Peripartum Events Scale. Paired maternal and cord blood and infant venous blood samples were collected. During the breastfeeding period, we monitored serum lithium and creatinine concentrations in mother–infant pairs at delivery, and at days 1–5, 7–11, 30, and 60 postpartum, and monthly until 6-months. Results: Lithium equilibrated completely across the placenta [1.13 (0.10), range (1.02–1.30)]. No women presented symptoms of postpartum lithium intoxication, two of the neonates presented transient hypotonia (22%). Lithium exposure was significantly less during breastfeeding than during late pregnancy, and serum lithium concentrations decreased up to 44% overtime from delivery to the first-month, and up to 60% to the third-month postpartum. There was no growth or developmental delay in the follow-up period. One woman had a manic episode with psychotic features at 45 days postpartum. Conclusions: In carefully selected women with bipolar disorder, lithium therapy when breastfeeding can be an appropriate option if coupled with close monitoring of the mother-infant pair.